Synthesis and characterization of TAPO-31 molecular sieves using tripropylamine template - Venkatathri, N.; Shetty, V. N. (Catalysis Communications, 2006)
TAPO-31 was synthesized hydrothermally using a novel template tri-n-propylamine for the first time. C and N analysis shows the butanol from titanium tetrabutoxide plays an important role in the synthesis. The incorporation of titanium into framework of phosphorous and both aluminiurn and phosphorous sites was suggested from elemental analysis. Isomorphous substitution of titanium (III) in AlPO framework was confirmed from ESR and (31)p MASNMR spectra. UV-Vis and XPS spectra revealed a partial oxidation of framework titanium (III) into titanium (IV) in the calcined TAPO-31 and thus the presence of redox centers in the products. The higher titanium content (Al/Ti = 10) TAPO-31 sample shows higher activity for phenol hydroxylation compared to lower titanium content (Al/Ti = 20) and Titanium impregnated AIPO(4)-31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ESR; FT-IR; MASNMR; SEM; TAPO-31; TG/DTA; tripropylamine; UV-Vis; XPS; XRD

Synthesis, characterization and catalytic properties of vanadium aluminophosphate molecular sieves VAPO-31 and VAPSO-Amr from non-aqueous media - Venkatathri, N. (Applied Catalysis A-General, 2006)
Vanadium samples containing aluminophosphate molecular sieve (VAPO-31) and amorphous vanadium silicoaluminophosphate (VAPSO-Amr) have been synthesized using hexamethyleneimine template from non-aqueous media for the first time. XRD and SEM analyses confirm the phase purity of the synthesized samples. FT-IR analysis suggests the incorporation of V4+ in the aluminophosphate framework. ESR, UV-vis spectroscopic, and XPS techniques and cyclicvoltametric studies confirm the incorporation of vanadium and reveal its presence in tetrahedral and square pyramidal environments in the as-synthesized samples. Cyclic voltammetry reveals the presence of two redox couples in VAPO-31. This catalyst is found to be a good oxidation catalyst. Although most of the properties of VAPO-31NA and VAPSO-Amr are similar, the latter can access more vanadium and V4+ ions. Compared to aqueous media samples, it can incorporate more vanadium especially V5+, ions and has been found to be better oxidation catalyst. The physicochemical properties also change with media. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cyclic voltammetry; ESR; FT-IR; MAS NMR; non-aqueous; SEM; TG/DTA; UV-Vis; VAPO-31; XPS; XRD

Influence of dopant ions on properties of conducting polypyrrole and its electrocatalytic activity towards methanol oxidation - Adhikari, Arindam; Radhakrishnan, S.; Patil, Rahul (Synthetic Metals, 2009)
The polypyrrole (PPy) films were deposited on vacuum metallized substrates by electro-oxidation of pyrrole monomer. These electrodes were then modified with a range of metal halides having different electronegativities. The modified polypyrrole electrodes were employed to investigate electrocatalytic activity towards methanol electrochemical oxidation by means of cyclic voltammetry in 0.1 M HClO(4) as supporting electrolyte. It was found that the electronegativity of the dopant ion incorporated in the PPy film governs the electrocatalytic activity towards methanol oxidation. Among different dopant anions used in the present work, the PPy doped with zirconium chloride gave the highest anodic current of 10 mA cm(-2) at the oxidation potential of methanol. Electrical property and the charge created due to doping in the polymers were measured using X-ray photoelectron spectroscopy (XPS) and Electron spin resonance spectroscopy (ESR). Electrocatalytic activity of the modified electrodes was correlated with various factors obtained from different polymer characterization experiments. The results were explained on the basis of the charge-transfer efficiency at the electrode I electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: charge transfer; electrocatalyst; ESR; Metal halide dopant; Methanol oxidation; polypyrrole; XPS